2019
DOI: 10.1678/rheology.47.143
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inertia on Linear Viscoelasticity of Harmonic Dumbbell Model

Abstract: The overdamped (inertialess) dumbbell model is widely utilized to study rheological properties of polymers or other soft matters. In most cases, the effect of inertia is merely neglected because the momentum relaxation is much faster than the bond relaxation. We theoretically analyze the effect of inertia on the linear viscoelasticity of the harmonic dumbbell model. We show that the momentum and bond relaxation modes are kinetically coupled and the inertia can affect the bond relaxation if the momentum relaxat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…(The superscript "(UD)" means the underdamped system.) The single dumbbell stress tensor can be decomposed into the contributions of the center of mass and the bond vector as [3]:…”
Section: Virtual Work Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(The superscript "(UD)" means the underdamped system.) The single dumbbell stress tensor can be decomposed into the contributions of the center of mass and the bond vector as [3]:…”
Section: Virtual Work Methodsmentioning
confidence: 99%
“…The dynamic equations ( 4) and ( 5) can be decomposed into two set of statistically independent equations. We introduce the center of mass position R(t) ≡ [R 1 (t) + R 2 (t)]/2 and the bond vector r(t) ≡ R 2 (t) − R 1 (t) [3]. We also introduce the momenta for the center of mass and the bond vector, P (t) ≡ P 1 (t) + P 2 (t) and p(t) ≡ [P 2 (t) − P 1 (t)]/2.…”
Section: Flexible Dumbbell With Tethering Potentialmentioning
confidence: 99%
“…The contribution of the kinetic part stress per one particle reduces to −k B T1. 13) Thus the kinetic part stress tensor field should be defined as…”
Section: Theory 21 Microscopic Strain Tensor and Microscopic Stress T...mentioning
confidence: 99%
“…However, the memory kernel is difficult to handle with, and the memoryless Langevin equation under the Markovian approximation is widely employed as an approximate dynamic equation. (A recent work [39] showed that the generalized Langevin equation can be approximated by a Langevin equation with an effective mobility tensor, if the memory effect is weak.) Our derivation of the coarse-grained Langevin equation does not use the projection operator and simple (although the validity and accuracy of approximations are not fully justified).…”
Section: Coarse-grainingmentioning
confidence: 99%